Обучаемая модель вычислений на классификациях - Кравцов, Г.А.; Кошель, В.И.; Долгоруков, А.В.; Цуркан, В.В. (Електронне моделювання, 2018)
Рассмотрено классическое понятие меры в соответствии с условиями симметричности, рефлексивности и неравенства треугольника. Выдвинуты требования к мере для ее использования в теории вычислений на классификациях. Установлена ограниченность применения функций расстояния, коэффициента корреляции, косинусной меры подобия. Определена и проанализирована применимость используемых на практике мер сходства. Это позволило аргументировать необходимость введения новой меры. Дано формальное определение обучаемой модели вычислений на классификациях. Розглянуто класичне поняття міри відповідно до умов симетричності, рефлективності та нерівності трикутника. Висунуто вимогу до міри для її використання в теорії обчислень на класифікаціях. Встановлено обмеженість використання функцій відстані, коефіцієнта кореляції, косинусної міри подібності. Визначено та проаналізовано застосовність мір подібності, що використовуються на практиці. Це дозволило аргументувати необхідність введення нової міри. Наведено формальне визначення моделі обчислень на класифікаціях, яка навчається. The problem has been considered of constructing a class of codes with summation with the smallest total number of undetectable errors in data vectors for a given numbers of data and check bits. An algorithm is proposed for constructing modified modular codes with summation of weighted data bits with a sequence of weight coefficients that forms a natural series of numbers. Properties of a new class of codes are analyzed in comparison with known modular codes with summation of single indicators of digits. A classification and a detailed comparative analysis of modular codes with summation possessing the property of identifying any errors with odd multiplicities are given. The advantages and disadvantages of the new modified modular weighted codes with summation are shown.